Numerical Analysis and Its Applications 4th International Conference, NAA 2008, Lozenetz, Bulgaria, June 16-20, 2008. Revised Selected Papers - Margenov, Svetozar.; Vulkov, Lubin G.; Wa[niewski, Jerzy. (Lecture Notes in Computer Science, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International Conference on Numerical Analysis and Its Applications, NAA 2008, held in Lozenetz, Bulgaria in June 2008. The 61 revised full papers presented together with 13 invited papers were carefully selected during two rounds of reviewing and improvement. The papers address all current aspects of numerical analysis and discuss a wide range of problems concerning recent achievements in physics, chemistry, engineering, and economics. A special focus is given to numerical approximation and computational geometry, numerical linear algebra and numerical solution of transcendental equations, numerical methods for differential equations, numerical modeling, and high performance scientific computing.